UV-light-driven cadmium sulphide (CdS) nanocatalysts: synthesis, characterization, therapeutic and environmental applications; kinetics and thermodynamic study of photocatalytic degradation of Eosin B and Methyl Green dyes. (20th January 2022) - Ali, Sundas; Akbar Jan, F.; Ullah, Rahat; Wajidullah; Ullah, Naimat; Salman
Abstract: Cadmium sulphide (CdS) nanoparticles (NPs) were synthesized through hydrothermal route and characterized by UV-Vis spectroscopy, X-ray diffraction (XRD), Energy dispersive X-ray analysis, Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy and Thermo gravimetric analysis (TGA).The band gap of CdS nanoparticles was found to be 2.38 eV. CdS NPs are crystalline aggregates with hexagonal structure as shown by SEM and XRD analysis. TGA study revealed that the synthesized nanomaterials were very stable to temperature and only 6.54% total loss occurred during heating range (25 °C–600 °C).The CdS NPs were used for the first time against the degradation of Eosin B (EB) and Methyl green (MG) dyes in aqueous solution.The degradation of EB and MG over CdS nanocatalysts followed second order kinetics. The predicted activation energies for both the dyes' reactions were 61.1 kJ/mol and 32.11 kJ/mol, respectively. About 95% and 90% dye degradation was observed at the time interval of 160 minutes for EB and MG, respectively. High percent degradation of EB was observed at high pH (pH 0) while at low pH (pH 4) high percent degradation was found for MG dye. Maximum dye degradation was found at the optimal dose (0.03 g/L) of the catalyst and at low dye concentration. The rate of EB and MG dye degradation was found to increase with increase in temperature up to 45 °C. The recyclability study showed that CdS nanoparticles could be reused for the degradation of the given dyes. Good antibacterial activity against Staphylococcus aureus was shown by CdS NPs. From the biocompatibility it was confirmed that CdS NPS are bioincompatible compatible. HIGHLIGHTS: The band gap was 2.38 eV. Dyes degradation over followed second order kinetics. 61.1 kJ/mol and 32.11 kJ/mol were activation energies. 95% and 90% dye degradation was observed for EB and MG, respectively. Good antibacterial activity against Staphylococcus aureus . CdS NPS were found bioincompatible compatible.